Dust Structure Nearby G229-03 - Shrestha, Hem; Jha, Ajay Kumar; Nepal, Saroj; Tiwari, Aatmaram; Bantawa, Kamana; Limbu, Dhiren Subba (Himalayan Journal of Science and Technology, 2021)
The Sky View Virtual Observatory was used for the systematic search of dust structures within the far-infrared loop G229-03. The source (object) responsible for the formation of the cavity of interest was detected by the Set of Identifications, Measurements, and Bibliography for Astronomical Data (SIMBAD) database. The total mass of the loop was 8.50031 × 1029 kg which is about 0.425 times the mass of the Sun at a distance of 1300 pc. The size of the cavity was 3.67° × 3.6°, whereas its core size was 0.531° × 0.255° located at R.A. (J2000) = 7h10m0.8s and Dec.(J2000) =15h55m30s. The minimum and maximum temperatures were between 20.24 ± 1.16 K and 18.63 ± 1.96 K respectively. In the core region, the average temperature was 19.53 K, approximately equal to Gaussian center 19.267 K with an offset temperature of 0.4 K showing that the core region of the cavity is dynamically stable. The Far-infrared loop was found to be located within a 1° radius around the high-velocity cloud HVC oriented by 45° to the plane of the sky. The inclination angle of the core of the loop was greater than 60° whereas the inclination angle for the larger structure was 13.71°. The Gaussian distribution of temperature was well fitted with the center of 19.267 K which shows that the cavity was in thermal equilibrium and the outer region with offset temperature of about 35 K suggesting that the loop was dynamically unstable possibly due to high-velocity cloud